Effects of Surgery on Survival of Early-Stage Patients With SCLC: Propensity Score Analysis and Nomogram Construction in SEER Database - Wang, Yuyan; Zheng, Qiwen; Jia, Bo; An, Tongtong; Zhao, Jun; Wu, Meina; Zhuo, Minglei; Li, Jianjie; Zhong, Jia; Chen, Hanxiao; Yang, Xue; Chi, Yujia; et al. (Frontiers in Oncology, 2020)
Purpose: The aim of this study was to assess the survival beneﬁt of surgery for patients with stage IA-IIB SCLC and build a nomogram to predict the overall survival (OS). Methods: Patients diagnosed with stage IA-IIB SCLC between 2004 and 2014 and received active treatment were selected from the SEER database. The primary endpoint was OS. The associations between surgery (or no surgery) and OS were compared using Cox proportional hazards models and propensity score analyses. A nomogram was constructed for predicting 1- and 3-year OS probability. Results: 2,246 patients were reviewed in our study. The median OS was 35 months and 19 months in surgery and non-surgery groups, respectively. Multivariable Cox proportional hazards models showed a survival benefit in the surgery group (HR, 0.642; 95% CI, 0.557-0.740; P < 0.001). Additionally, in order to balance measurable confounders between groups, propensity score (PS) matching was employed to assess the impact of surgery on OS. After PS matching, overall survival analysis still favored surgical resection. The PS-stratification model, PS-weighting, and PS-adjustment model showed similar results to demonstrate a statistically significant benefit for surgery. Further nomogram was well calibrated, and had good discriminative ability, with c-index of 0.645 for OS. Conclusion: Our analysis suggests surgery is a viable option for early stage SCLC patients with possible improvements in clinical outcomes for surgical patients. Our nomogram provides a valuable tool for better evaluation of OS and assists clinicians involved in treatment planning.